Effects of feeding regime and ecological location on the chemical profile of honey: a multidimensional compositional evaluation - Ugur, Yilmaz; Avcu, Fatih Mehmet; Zengin, Rukiye; Basgel, Serkan; Demir, Nurullah; Maras, Zeynep; Erdogan, Selim (Springer, 2026)
Understanding how production-related and ecological factors influence honey composition is important for quality evaluation and authenticity-oriented interpretation. This study examined the combined effects of four feeding regimes (control, glucose, sucrose, and bee feed) and two ecological locations (Bu & gbreve;day Deresi and Uluk & ouml;y, T & uuml;rkiye) on the chemical and biochemical properties of honey. Sugar composition, phenolic compounds, mineral content, enzymatic activity, total phenolic and flavonoid contents, and antioxidant capacity were determined using chromatographic, spectrometric, and spectrophotometric methods. Feeding regime, ecological location, and their interaction significantly affected multiple compositional parameters. Honey from control colonies generally showed higher enzymatic, phenolic, and antioxidant values than honey from colonies receiving artificial carbohydrate supplements; for example, invertase activity decreased from 22.5 +/- 3.1 IN in the control group to 8.3 +/- 0.7 IN in the bee feed group, while CUPRAC values declined from 250.7 +/- 8.0 to 100.9 +/- 10.6 mg TE/kg. Bu & gbreve;day Deresi samples also showed higher total phenolic content than Uluk & ouml;y samples (294.8 +/- 15.5 and 227.8 +/- 5.0 mg GAE/kg, respectively). Multivariate analysis further confirmed that feeding regime and ecological location contributed to the differentiation of honey samples based on their integrated chemical profiles.
Keywords: Honey; Authenticity; Feeding Regime; Chemical Fingerprinting; Phenolic Profile; Geographical Origin